Comparison of the immunogenicity and safety of the purified chick embryo cell rabies vaccine manufactured in India and Germany: A randomized, single blind, multicentre, phase IV clinical study - Gadey Sampath; Angelika Banzhoff; Alaka Deshpande; Claudius Malerczyk; Ashwani Kumar Arora; Hoshang Vakil; Scott Preiss (Taylor & Francis Group, 2017)
This phase IV, single blind study assessed the immunogenicity and safety of India-manufactured purified chick embryo cell rabies vaccine (PCECV), compared with a German-manufactured batch obtained by the same production process. A total of 340 participants enrolled at 2 study sites in India were randomized (1:1:1:1) in 4 groups to receive a 5-dose Essen regimen with either 1 of the 3 Indian batches (PCECV-I) or the German batch (PCECV-G), administered on Days (D) 0, 3, 7, 14 and 30. The lot-to-lot consistency of PCECV-I batches in terms of induced immune response at D14 was demonstrated. The immune response elicited by PCECV-I was shown to be non-inferior to that induced by PCECV-G, as the lower limit of the 95% confidence interval for the ratio (PCECV-I/PCECV-G) of rabies virus neutralising antibody (RVNA) geometric mean concentrations was higher than 0.5 at D14. At least 96% of participants developed adequate RVNA concentrations (≥ 0.5 IU/mL) by D14 and all achieved RVNA concentrations ≥ 0.5 IU/mL by D90. RVNA levels were comparable across all groups throughout the entire study. Solicited local and general symptoms had a similar incidence in all groups. Unsolicited adverse events (AEs) were reported by 11% of participants. Only 1 serious AE (leg fracture) was reported and was not related to vaccination. No deaths and no rabies cases were recorded during the 90 days of observation. The study showed that the 3 PCECV-I and the PCECV-G batches induced a similar immune response and had a comparable safety profile when administered according to a 5-dose schedule.